Sex and international tribunals : the erasure of gender from the war narrative - Mibenge, Chiseche Salome (Pennsylvania studies in human rights., 2013)
In this book, the author applies stringent analysis to the humanitarian but flawed legal narratives of sexual violence in Rwanda and Sierra Leone, calling for more nuanced analysis of how gender shapes violence and access to justice for survivors.